Intergenerational Rift in Russian Village: Impact of “Anti-Religious Offensive” of Communist Youth at Turn of the 1920—1930s - A. A. Slezin (Научный диалог, 2023)
The article is devoted to the analysis of the relationship in the spiritual sphere between the representatives of the peasant generation of the “revolutionary turning point” (born at the turn of the XIX—XX centuries) and Komsomol members from the generation of “children of the revolution” (their childhood fell on the first post-revolutionary years) in the initial period of mass collectivization of the USSR. The deep demographic changes in post-revolutionary Russia, the strengthening of the role of youth in the countryside are shown. A statistical analysis of rural Komsomol organizations was carried out. Young people are seen as a demographic group that has formed a critical attitude towards religion. Komsomol is recognized as an organization that turned the generational hierarchy of the Russian village. Much attention is paid to the role of the Union of Militant Atheists in attracting young people to active anti-religious activities. Priority is given to studying the reaction of peasants to the antireligious activities of youth. It is shown that the spiritual heritage, which, according to the rules of continuity of development, the generation of the “revolutionary turning point” was called upon to pass on to its successors, was rejected in real life by active representatives of the younger generation. From the author’s point of view, the participation of young people in the “anti-religious offensive” is one of the decisive factors in the strengthening of the intergenerational rift, which became apparent even in the previous decade.